Development and Application of the Owner-Bird Relationship Scale (OBRS) to Assess the Relation of Humans to Their Pet Birds - Burmeister, Anne-Kathrin; Drasch, Katrin; Rinder, Monika; Prechsl, Sebastian; Peschel, Andrea; Korbel, Rüdiger; Saam, Nicole J. (Frontiers in Veterinary Science, 2020)
Humans and birds have lived together from time immemorial. Despite this long history, only a few birds besides domestic pigeons and poultry can be described as domesticated. Therefore, living with a pet bird can be challenging, and the human-avian relationship has a major influence on the quality of this cohabitation. There are, however, only few studies focusing on the characterization of this relationship so far, and these studies generally used scales developed for dogs and cats or other domesticated companion animals and might not be appropriate to identify important specific features of the human-pet bird relationship. Following a sociological approach, a concept of human-animal relationship was developed leading to three types of human-animal relationship (impersonal, personal and close personal human-animal relationship). This concept was used to develop a 21-item owner-bird-relationship scale (OBRS). This scale was applied to measure the relationship between bird-keeping pet owners (keepers) and their birds in an online survey performed in Germany which comprised 1,444 bird owners. Factor analysis revealed that the relationship between owner and bird consisted of four dimensions: the tendency of the owner to anthropomorphize the bird; the social support the bird provides for the keeper; the empathy, attentiveness, and respect of the keeper towards the bird; and the relationship of the bird towards the owner. In the sample of German bird owners, more than one quarter of the bird keepers showed an impersonal, half a personal, and less than a quarter a close personal relationship to their bird. The relationship varied with the socio-demographic characteristics of the owners, such as gender, marital status, and education. This scale supports more comprehensive quantitative research into the human-bird relationship in the broad field of human-animal studies including the psychology and sociology of animals as well as animal welfare and veterinary medicine.